Environmental safety as a priority factor of international relations under the conditions of globalization: parity basis and principles of formation - Obikhod, A.; Omelchenko, A.; Boiko, V. (Економіка природокористування і охорони довкілля, 2015)
The article examines prerequisites for the formation of the global environmental safety as an integral part of international relations and politics against the background of the long-term ecological crisis. Features of the global environmental safety and levels of its operation on a territorial basis are singled out and grounded. Attention is focused on transboundary character of the manifestation of most environmental threats and hazards, making it impossible for countries to overcome the consequences on their own. Emphasized are global threats and hazards that will determine areas of cooperation in the global environmental safety in the near future. Parity basis and principles of formation of global ecologically safe space are outlined. Considering the world experience of the implementation of forms and methods of economical use of natural resources and observance of safety of existence, directions of strategic planning of national environmental safety are suggested. Розкриваються передумови становлення глобальної екологічної безпеки як невід’ємної частини міжнародних відносин та політики на фоні довготривалої екологічної кризи. Виділяються та обґрунтовуються характерні ознаки глобальної екологічної безпеки та рівні її функціонування за територіальним принципом. Акцентується увага на транскордонності прояву більшості екологічних загроз та небезпек, що унеможливлює подолання наслідків державами самостійно. Виділено глобальні загрози та небезпеки, що визначатимуть у найближчій перспективі напрями співпраці у світовій екологічній безпеці. Окреслюються паритетні засади та принципи формування глобального екологобезпечного простору. Виходячи із світового досвіду форм і методів ощадливого використання природних ресурсів та дотримання безпеки існування, запропоновано напрями стратегічного планування національної екологічної безпеки.